2011
DOI: 10.1016/j.devcel.2011.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Regulation of Emi2 by Emi2-Bound Cdk1/Plk1/CK1 and PP2A-B56 in Meiotic Arrest of Xenopus Eggs

Abstract: In vertebrates, unfertilized eggs are arrested at metaphase of meiosis II by Mos and Emi2, an inhibitor of the APC/C ubiquitin ligase. In Xenopus, Cdk1 phosphorylates Emi2 and both destabilizes and inactivates it, whereas Mos recruits PP2A phosphatase to antagonize the Cdk1 phosphorylation. However, how Cdk1 phosphorylation inhibits Emi2 is largely unknown. Here we show that multiple N-terminal Cdk1 phosphorylation motifs bind cyclin B1-Cdk1 itself, Plk1, and CK1δ/ε to inhibit Emi2. Plk1, after rebinding to ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 48 publications
5
44
0
Order By: Relevance
“…This caused a decrease in the level of cyclin synthesized when proteasome activity was permitted (Figure 4C, left, boxes), whereas blocking the proteasome (Figure 4C, left, open circles) caused accumulation of cyclin that matched levels seen in extracts with unaltered CDK1 activities. This confirmed that increasing CDK1 activity can increase APC activity in CSF extracts—which had been reported previously (Hansen et al , 2007; Wu et al , 2007; Isoda et al , 2011)—but did not slow the production of cyclin B. This is the opposite of what we observed prior to and during M phase of mitotic cycles and demonstrates that CDK1 activity does not exert the same inhibition on cyclin synthesis in mature oocytes/eggs (CSF extract) that it does in embryos (cycling extract).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This caused a decrease in the level of cyclin synthesized when proteasome activity was permitted (Figure 4C, left, boxes), whereas blocking the proteasome (Figure 4C, left, open circles) caused accumulation of cyclin that matched levels seen in extracts with unaltered CDK1 activities. This confirmed that increasing CDK1 activity can increase APC activity in CSF extracts—which had been reported previously (Hansen et al , 2007; Wu et al , 2007; Isoda et al , 2011)—but did not slow the production of cyclin B. This is the opposite of what we observed prior to and during M phase of mitotic cycles and demonstrates that CDK1 activity does not exert the same inhibition on cyclin synthesis in mature oocytes/eggs (CSF extract) that it does in embryos (cycling extract).…”
Section: Resultssupporting
confidence: 90%
“…The control of meiotic cyclin B translation in the unfertilized egg, however, is different from that of mitotic cycles. Polyadenylation of cyclin B1 mRNA has been reported in the unfertilized egg (Sheets et al , 1994; Ballantyne et al , 1997; Kim and Richter, 2007; Belloc et al , 2008), and we confirmed that meiotic CSF extracts are capable of continuous cyclin translation in the presence of elevated CDK1 activity, in agreement with previously published studies (Hansen et al , 2007; Wu et al , 2007; Isoda et al , 2011). Therefore, although translation of cyclin B in meiotic M phase is continuous despite CDK1 activity, it is attenuated during M phase of mitotic cycles.…”
Section: Discussionsupporting
confidence: 93%
“…However, cyclin:Cdk kinase activity phosphorylates certain APC/C subunits, such as Cdc27, as well as phosphorylating and inactivating an inhibitor of the APC/C, Emi2 [30, 31]. We suggest that Cyclin B3:Cdk1 has unique substrate specificity [32] and spatial-temporal distribution that make it an effective activator of APC/C.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that TAM could regulate OSD1 to prevent precocious meiotic exit. Alternatively, phosphorylation by TAM could inactivate OSD1 and thus allow exit from meiosis I. Interestingly, the activity and stability of Emi2/Erp1 - the vertebrate meiotic APC/C inhibitor - is regulated by phosphorylation [33], [34]. Further functional analysis of the OSD1 putative phosphorylation sites is required to establish the role of this CYCA1;2/TAM-CDKA;1-mediated phosphorylation in meiotic cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%